2008
DOI: 10.1128/jvi.01192-08
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Avian Influenza Virus Induces Apoptotic Cell Death in Mammalian Airway Epithelial Cells

Abstract: In recent years, the highly pathogenic avian influenza virus H5N1 has raised serious worldwide concern about an influenza pandemic; however, the biology of H5N1 pathogenesis is largely unknown. To elucidate the mechanism of H5N1 pathogenesis, we prepared primary airway epithelial cells from alveolar tissues from 1-year-old pigs and measured the growth kinetics of three avian H5 influenza viruses ( These results suggest that only H5N1 induces apoptosis in pAEpC. H5N1 cytopathicity was inhibited by adding the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 62 publications
5
60
0
Order By: Relevance
“…A similar phenomenon is observed in bovine mastitis, in which bacterial infection damages the blood-milk barrier resulting in increased pH values in milk (50). We previously reported that H5N1 viruses induce apoptosis in duck embryonic fibroblasts and mammalian airway epithelial cells (10,51), supporting the hypothesis that luminal pH changes occur in the intestine of H5N1-infected birds.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A similar phenomenon is observed in bovine mastitis, in which bacterial infection damages the blood-milk barrier resulting in increased pH values in milk (50). We previously reported that H5N1 viruses induce apoptosis in duck embryonic fibroblasts and mammalian airway epithelial cells (10,51), supporting the hypothesis that luminal pH changes occur in the intestine of H5N1-infected birds.…”
Section: Discussionsupporting
confidence: 50%
“…Viruses and Cells-Influenza virus strains A/crow/Kyoto/ 53/04 (H5N1) (Cw/Ky (H5N1)) and A/chicken/Egypt/CL6/07 (H5N1) (Ck/Eg (H5N1)) were isolated from embryonated chicken eggs inoculated with tracheal or lung homogenates from dead crows (10) or dead chickens (11), respectively. A/Beijing/262/95 (H1N1) (Beijing (H1N1)), A/Duck/Hong Kong/ 273/78 (H2N2) (Dk/Hk (H2N2)), A/Panama/2007/99 (H3N2) (Panama (H3N2)), A/Duck/Hong Kong/668/79 (H4N5) (Dk/ Hk (H4N5)), A/Duck/Hong Kong/820/80 (H5N3) (Dk/Hk (H5N3)), A/Turkey/Ontario/7732/66 (H5N9) (Tk/Ont (H5N9)), A/Duck/Hong Kong/960/80 (H6N2) (Dk/Hk (H6N2)), A/wigeon/ Osaka/1/01 (H7N7) (Wg/Os (H7N7)), A/Turkey/Ontario/6118/67 (H8N4) (Tk/Ont (H8N4)), and A/Duck/Hong Kong/448/78 (H9N2) (Dk/Hk (H9N2)) were kind gifts from Yoshinobu Okuno (Kanonji Institute, the Research Foundation for Microbial Diseases of Osaka University, Kagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In influenza virus pneumonia, alveolar epithelial cell apoptosis is induced by macrophages through the release of tumor necrosis factor-related apoptosis-inducing ligand (6). Avian influenza A virus H5N1 induces apoptosis in alveolar epithelial cells via the caspase-dependent pathway (9). PolyI:C, an analog of dsRNA, can induce a marked inflammatory response in the lungs and lead to impairment of pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory epithelial cells are the major target of viral replication (8). In vitro, the H5N1 subtype of the influenza virus causes substantial death of mammalian airway epithelial cells due to the induction of apoptosis (9). The apoptosis or death of the alveolar epithelium, especially, ATII cells, is an underlying mechanism of alveolar damage in murine and human influenza virus infections (10).…”
Section: Introductionmentioning
confidence: 99%